Insights into HPLC-MS/MS Analysis, Antioxidant and Cytotoxic Activity of Astragalus fruticosus against Different Types of Cancer Cell Lines - Mohamed Fayez Dekinash; Tarek M. Okda; Ehab Kotb Elmahallawy; Fathy Kandil El-Fiky; Gamal Abd El Hay Omran; Emil Svajdlenka; Naief Dahran; Manal F. El-Khadragy; Wafa A. Al-Megrin; El Moataz Bellah Ali El Naggar (MDPI AG, 2022)
Plants from the genus Astragalus are gaining attention for their pharmacological importance. However, the information available regarding the HPLC-MS/MS chemical profile of A. fruticosus is inadequate. In this study, we performed HPLC-MS/MS analysis using electrospray ionization (ESI) and atmospheric pressure chemical ionization (APCI). We tentatively identified 11 compounds in the A. fruticosus methanolic extract, including five flavonoidal and six saponin glycosides. The extract showed moderate antioxidant activity with 21.05% reduction in DPPH UV absorption. The preliminary cytotoxic screening against seven human cancer cell lines using 100 μg/mL extract showed prominent cytotoxic potential against colorectal cancer HCT-116 with 3.368% cell viability. It also showed moderate cytotoxic potential against prostate (DU-145), ovarian (SKOV-3) and lung (A-549) cancer cell lines with cell viability of 14.25%, 16.02% and 27.24%, respectively. The IC50 of the total extract against HCT-116 and DU-145 cell lines were 7.81 μg/mL and 40.79 μg/mL, respectively. The observed cytotoxicity of the total methanolic extract from the leaves against colorectal cancer might facilitate future investigations on cytotoxic agent(s) for disease management.